Designing 2D–2D g-C3N4/Ag:ZnIn2S4 nanocomposites for the high-performance conversion of sunlight energy into hydrogen fuel and the meaningful reduction of pollution. Issue 54 (3rd September 2020) - Gao, Yu; Qian, Kun; Xu, Baotong; Ding, Fu; Dragutan, Valerian; Dragutan, Ileana; Sun, Yaguang; Xu, Zhenhe
Abstract : The generation of hydrogen-based energy and environmental remediation using sunlight is an emerging topic of great significance for meeting the ever-growing global need. Abstract : The generation of hydrogen-based energy and environmental remediation using sunlight is an emerging topic of great significance for meeting the ever-growing global need. However, the actual photocatalytic performance is still far below expectations because of the relatively slack charge-carrier separation and migration as well as insufficient spectral absorption in semiconductors. Therefore, the rational construction of heterojunctions is considered as an effective approach to solving the above issues. In this context, we have, for the first time, designed and synthesized a two-dimensional 2D-on-2D heterostructure, based on 2D Ag-doped ZnIn2 S4 nanoplates deposited on 2D g-C3 N4 nanosheets (denoted as g-C3 N4 /Ag:ZnIn2 S4 ). This construct benefits from improved visible-light absorption by unveiling a greater number of catalytically active sites, effectively enhancing charge-carrier separation and relocation. Detailed analysis has proved that under visible-light irradiation, the optimized g-C3 N4 /20 wt% Ag:ZnIn2 S4 nanocomposite has substantially upgraded photocatalytic activity in hydrogen formation by water splitting (hydrogen evolution rate of up to 597.47 μmol h −1 g −1 ) and in residual dyestuff degradation (methyl orange, MO; degradation rate constant of 0.1406 min −1 ). Noteworthily, these two exceptionally high values respectively represent 30.73 and 5.42 times enhancements vs. results obtained with bare g-C3 N4 . Another strong point of our g-C3 N4 /Ag:ZnIn2 S4 is its impressive recyclability for 20 runs, with no relevant metal release in the aqueous solution following photocatalysis. This work introduces new, superior access to highly efficient photocatalysts founded on 2D/2D nanocomposites serving both the production of hydrogen as an energy carrier and environmental remediation.